2013
DOI: 10.1108/jadee-12-2012-0031
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of a supply chain for organic vegetables from a smallholder perspective

Abstract: Purpose -The purpose of this paper is to identify factors that constrain marketing choices available to smallholders, limiting the chain's robustness from their perspective. Design/methodology/approach -This paper draws on transaction cost economics to develop a model explaining dyadic relationships between smallholders and their buyers. The model was used to analyse a case study of the supply chain for organic fresh vegetables in Kathmandu, Nepal. Findings -This chain is characterised mainly by relational con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Therefore agri-food industries should make adequate contributions to the welfare of associated communities. However, it is argued that the transformation process has given rise to several social challenges, under the influences of which social contributions from agri-food industries have become inadequate (Bhattarai et al 2013). These challenges include unemployment, low wages, child labour, gender imbalance, worker safety and welfare.…”
Section: Social Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore agri-food industries should make adequate contributions to the welfare of associated communities. However, it is argued that the transformation process has given rise to several social challenges, under the influences of which social contributions from agri-food industries have become inadequate (Bhattarai et al 2013). These challenges include unemployment, low wages, child labour, gender imbalance, worker safety and welfare.…”
Section: Social Challengesmentioning
confidence: 99%
“…According to Bhattarai et al (2013), inadequate information sharing provides opportunities for informed actors in the chain to exploit others. Grimm et al (2014) went further, to state that this had become a critical barrier to the development of sustainable value chains.…”
Section: Figure 63: Underlying Sub-themes Of Value Chain Constraintsmentioning
confidence: 99%
“…Transaction costs are influenced by the characteristics of the transaction, product and environment within which transactions occur (Bhattarai et al, 2013). These are asset specificity, frequency and uncertainty as the three most important characteristics of transactions that alter the cost of engaging in an exchange.…”
Section: Theoretical Perspectives Of Contract Farmingmentioning
confidence: 99%
“…The seasonality and perishability of agricultural products also increases the complexity of transacting, particularly when markets require specific quality standards and credence attributes in products. Complexity increases transaction costs by increasing the uncertainty of supply, by increasing information and monitoring costs, by increasing the need for assets that have little value in alternative uses, and by increasing the cost of renegotiating incomplete contracts ex post (Bhattarai et al, 2013).…”
Section: Theoretical Perspectives Of Contract Farmingmentioning
confidence: 99%
“…This chain is characterised mainly by relational contracting between smallholders and their buyers. There was also evidence of vertical integration by some buyers, and of growers selling on informal markets (Bhattarai et al, 2013). Lohmann and Foster (2006) compare niche and mainstream of marketing strategies in UK and Germany found that considers the present situation and future challenges of organic food, In the UK, there is potential for the expansion of small-scale, decentralized marketing outlets, while in Germany greater involvement by supermarkets appears to be appropriate.…”
mentioning
confidence: 99%